Characterization of the Volatile Compounds of Zhenba Bacon at Different Process Stages Using GC–MS and GC–IMS - Linjie Xi; Jing Zhang; Ruixiao Wu; Tian Wang; Wu Ding (Foods, 2021)
Zhenba bacon (ZB), a type of Chinese traditional bacon with a long history, has attracted considerable attention in the Southwest of China for its unique flavor. To elucidate the changing course of aroma components during the process of ZB, four stages of process stages were assessed by GC–MS and GC–IMS coupled with multivariate data analysis. A total of 44 volatile compounds were identified by GC–IMS, including 5 esters, 8 alcohols, 12 aldehydes, 3 ketones, 1 furan and 2 sulfides; 40 volatile compounds were identified by GC–MS, 4 ketones, 7 phenols, 8 alcohols, 6 esters, 6 aldehydes, and 6 other compounds were detected. During the curing period, the amount and content of esters in Zhenba bacon gradually increased. Phenols appear in large quantities during the smoking period. The VOCs (volatile organic compounds) in the gallery plots were the most diverse in YZ samples, which are mainly esters. POV (peroxide value) and TBARS (thiobarbituric acid reactive substance) showed that lipid oxidation played an important role in the formation of volatile flavor components of bacon. This study provides valuable analytical data to explain the flavor formation of Zhenba bacon.